Expanding Sexual Selection Gradients; A Synthetic Refinement of Sexual Selection Theory. (23rd January 2015) - Fitzpatrick, Courtney L.; Hauber, M.
Abstract Sexual selection is usually modeled as fitness differences that are mediated through variation in the number of mates obtained (variance in mating success, VMS). Nevertheless, empirical studies increasingly posit sexual selection even when VMS is low or does not contribute to variance in fitness, as is the case in females of many species. In these contexts, evolution by sexual selection is only plausible if it is mediated through variation in mate quality (VMQ) rather than exclusively through variation in the number of mates (VMS). However, we lack a formal theoretical foundation for sexual selection in these cases. Here, I argue the need for an explicit, formal treatment of how VMQ may result in sexual selection. Building upon the conceptually powerful framework of sexual selection gradients, I propose a graphical heuristic model that aims to serve as a foundation for future formal models. I close by discussing the implications of this perspective for sexual selection research in general, with particular attention to predictions that the model generates for the action of sexual selection on female traits.